The global factor : issues and images in international law - Hewison, Grant (Redfern, N.S.W. : Redfern Legal Centre Publishing, 1989)
Introductory guide to International law, developed as a project for the International Year of Peace (1986) ; includes "Case Study: Black War in Tasmania" (pp.55-56) and "Makarrata - An Aboriginal Treaty" (pp.61-69).
Includes index.
Bibliography: p. 138-140.
Keywords: International law; International organization; Law - International law - UN conventions; Government policy - Self management; Politics and Government - Sovereignty; Law - Constitutional law - Treaty movement; Law - International law - Human rights; Tasmania (Tas); Australia